Honey quality of Melipona sp. bees in Acre, Brazil (2018)
Honey from stingless bees (Melipona sp.) is a nutritious and medicinal product economically valued in the informal Brazilian market, driven by the growing demand for natural products; however, its physicochemical characteristics are still unknown. Thus, the aim of this study is to evaluate the physicochemical profile of the stingless bee honey produced in Cruzeiro do Sul, Acre. Honey samples were analyzed following the methodology recommended by Ministério da Agricultura, Pecuária e Abastecimento; the following parameters were established: moisture, total sugars, reducing sugars, apparent sucrose, ash, crude protein, diastase activity, Brix degrees, free acidity, lactonic acidity, total acidity, pH, hydroxymethylfurfural, electrical conductivity, color and Lugol, Lund and Fiehe reactions. Results show that these parameters are not suitable for all samples, being incompatible with established standards, indicating that the current legislation on Apis mellifera is not suitable for all characters analyzed, mainly moisture content, corroborating the need to standardize guidelines for honey from stingless bees. Moreover, there was no tampering in the honeys analyzed.